Pyrenophora tritici repentis, the causal agent of tan spot: a review of intraspecific genetic diversity - Moreno, María Virginia (2012)
In some countries where the wheat is cultivated, the biological adversities are led by foliar disease. These diseases have emerged as a serious problem in many areas where the wheat is the principal crop. In the last few years, minimum tillage has been considered advantageous to soil conservation, but it leads to a loss of available nutrients and a potential increase in necrotic pathogens whose saprophytic stage lives in the straw of the crop (Annone, 1985). Establishment of the crop under this management can be affected by pathogens of this type. Leaf spotting diseases can be caused by one or a combination of leaf spotting pathogens (Table 1). Leaf spotting diseases affect wheat grown reduce the photosynthetic area of leaves resulting in reduced grain filling and lower yields; particularly when the top two leaves (penultimate and flag leaves) are severely infected. The most of these diseases are similar in host symptomatology, disease cycle, life cycles of pathogens and types of damage induced. Whitin of these pathogens the Ascomycota fungus, Pyrenophora tritici-repentis (Ptr) (Died.) Drechs. It is a facultative pathogen whose asexual stage is Drechslera tritici-repentis (Dtr) (Died.). This pathogen is the causal agent of tan spot of wheat.